Rapid and specific detection of Streptococcus suis serotype 2 using a RPA–PfAgo system coupled with fluorescence and lateral flow dipstick - Wang, Kexin; Zhao, Xujie; Li, Jingjing; Zhou, Mingzhu; Jiao, Bingze; Bai, Yilin; Teng, Zhanwei; Chang, Meinan; Bai, Yueyu; Hu, Jianhe; Ding, Ke; Xia, Xiaojing (Frontiers in Veterinary Science, 2026)
ObjectiveTo develop and validate dual detection platforms integrating recombinase polymerase amplification (RPA) with Pyrococcus furiosus Argonaute (PfAgo) for the rapid and specific identification of Streptococcus suis serotype 2.MethodsThe conserved cps2J gene was selected as the molecular target. Key RPA parameters and PfAgo reaction conditions were systematically optimized, including temperature, reaction time, MnCl2 concentration, gDNA design and probe concentration. Specificity and sensitivity were evaluated using plasmid dilutions and multiple S. suis serotypes together with other common swine pathogens. A total of 41 clinical samples were also tested and compared with the national standard PCR assay (GB/T 19915.3–2005).ResultsTwo assay formats were established: real-time fluorescence system (RPA-PfAgo-RTF) and lateral flow dipstick system (RPA-PfAgo-LFD). The RPA-PfAgo-RTF assay achieved a detection limit of 100 copies/μL, while the RPA-PfAgo-LFD assay detected 102 copies/μL. Both formats showed high specificity without cross-reactivity. Among 41 field samples, six were SS2-positive, and results showed 100% agreement with the reference PCR method. Total detection time for either assay was < 1 h.ConclusionBoth assay formats provide rapid, sensitive, and accurate tools for SS2 detection suitable for laboratory use and on-farm point-of-care testing.